Is there any relationship between the attenuation of cerebral ischemia-reperfusion injury and serum YAP-1 levels? (Annals of Medical Research, 2024)
Aim: Cerebral ischaemia (CI) is one of the leading causes of death worldwide. Due to the long and costly treatment process after ischemia and the need for lifelong patient care, studies in this field are important. Explaining the mechanism of damage is valuable in terms of developing preventive applications in risky persons and accelerating the treatment processes of sick patients. The aim of this study was to evaluate the relationship between serum yes-associated protein 1 (YAP-1) level, an antiapoptotic marker, and cerebral ischemia-reperfusion (CI/R) injury. Materials and Methods: Wistar Albino adult (10 weeks old, 280-300 g) male rats were randomly assigned to Sham, CI, Asp+CI, and CI+Asp, with 24-hours and 7-day reperfusion periods (n=8). CI was created using the intra-arterial filament technique during 60 minutes, Asprosin (Asp) (1 µg/kg/day) injections were applied 3 days before or 3 days during of 24h and 7 days reperfusion. YAP- l levels were measured using customary ELISA kits. The Kruskal-Wallis test was used to compare differences between groups. p
Keywords: Brain; Cerebral ischemia; YAP-1; Apoptosis